P EFFECT OF SELF-CONCEPT AND INDEPENDENCE OF LEARNING OUTCOMES LEARNING CLASS VIII IPS SMP N 2 TIGO NAGARI Pasaman - Ashar, Ashar; Ansofino, Ansofino; Sumarni, Sumarni (Pendidikan Ekonomi, 2014)
ABSTRAKIssues that are examined in this study was to determine the extent of the influence of self-concept and self learning together on learning outcomes of students of SMP N 2 IPS Tigo Pasaman Nagari . This research is descriptive Associative . The population in this study were all students of SMP 2 Tigo Nagari Pasaman , with a sample of 92 respondents . The technique is simple random sampling sampling.jenis data used are primary and secondary data . Instruments . To determine the effect of self-concept and self learning on learning outcomes of students of SMP N 2 IPS Tigo Nagari Pasaman used the t test and F testThe study says that , the first variable self-concept significant and positive impact on learning outcomes IPS eighth grade students of SMP N 2 Tigo Nagari Pasaman . This is evidenced by the coefficient value of 0.648 and the value of t ( 9.280 ) > t table ( 1.662 ) . This means that if the concept of self is increased by 1 % and keep the results independent learning social studies students of SMP N 2 Tigo Nagari Pasaman will increase by 0.648 % . These two variables are independent learning significant and positive impact on learning outcomes IPS eighth grade students of SMP N 2 Tigo Nagari Pasaman . This is evidenced by the coefficient value of 0.692 and the value of t ( 10.048 ) > t table ( 1.662 ) . This means that if independent learning is increased by 1 % and keep the results of self-concept social studies eighth grade students of SMP N 2 Tigo Pasaman Nagari will be increased by 0,692 % . The third variable is the concept of self- learning and self-reliance has a significant and positive influence on the results of IPS Learning Class VIII students of SMP N 2 Tigo Nagari Pasaman with the value of F ( 355.846 ) > Ftable ( 3,947 ) and Sig ( 0.000 ) < Alpha ( 0.05 ) . The percentage of variable influence of self-concept and self learning on Learning Outcomes IPS Eighth Grade Students of SMP N 2 Tigo Pasaman Nagari is equal to 88.9 % , while the remaining 11.1 % is explained by other variables that are outside the studyResearchers suggest it to all the schools first teacher to help the students in shaping the personality of students . Provide guidance to the students to direct them to learn independently , so that it can learn well and obtain good learning outcomes as well .